Persistence and change of regional new business formation in the national league table - Michael Fritsch; Sandra Kublina (Friedrich Schiller University Jena, 2016)
We investigate persistence and change of the levels of regional new business formation in West Germany over a period of thirty years. Our indicator is the position of a region in the national ranking. As indicated by previous studies, we generally find a rather high level of persistence and confirm the role of several sources of this persistence, namely, persistence in regional determinants of new business formation, distinct regional cultures of entrepreneurship, and path dependence in new business formation activity. There are, however, also a number of regions that have moved up or down in the national ranking by a considerable number of positions. We find that main factors that are related to such rank changes are R&D activities, industry diversity, and regional wage levels.
Keywords: L26; R11; O11; 330; economic development; entrepreneurship; new business formation; regional growth regimes